Association Between Lumbar Spinal Degeneration and Anatomic Pelvic Parameters. Issue 6 (July 2018) - Strube, Patrick; Pumberger, Matthias; Sonnow, Lena; Zippelius, Timo; Nowack, Dimitri; Zahn, Robert K.; Putzier, Michael
Abstract : Study Design: Retrospective cohort study. Objective: The objective was to prove the association between anatomic pelvis parameters and specific types of lumbar spinal degeneration. Summary of Background Data: Different spinopelvic sagittal profile types are suggested to be associated with specific degenerative lumbar spine pathologies. Because pelvic morphology plays a key role defining the spinal shape as well as its load and function it thereby potentially predisposes the development of spinal degeneration. Materials and Methods: Patients with symptomatic lumbar spinal degeneration who were surgically treated in 2 spine departments from March 2011 until August 2016 were included in this retrospective analysis. Single-level degenerative pathologies were classified as lumbar disc herniation (LDH), degenerative disc disease (DDD), lumbar spinal stenosis (LSS), and degenerative spondylolisthesis (DSPL). The constant anatomic pelvic parameters pelvic incidence (PI), pelvic radius (PR), and sacral table angle (STA) were assessed in lateral radiographs of the lumbar spine and compared between the pathologies. Results: In total, 249 patients were assigned to the LDH (n=73), DDD (n=67), LSS (n=42), and DSPL (n=67) groups. Group comparisons revealed significant differences in the anatomic pelvic parameters PR (LDH, 139.5±10.8 mm; DDD, 135.9±14.0 mm; LSS, 127.8±14.3 mm; DSPL, 135.8±12.7 mm; P <0.001), PI (LDH, 53.1±10.0 degrees; DDD, 50.0±9.9 degrees; LSS, 54.5±9.6 degrees; DSPL, 57.1±10.8 degrees; P =0.001), and STA (LDH, 95.3±12.7 degrees; DDD, 105.4±9.0 degrees; LSS, 105.9±11.5 degrees; DSPL, 98.6±9.5 degrees; P <0.001). Post hoc tests indicated significant differences between the PR of the LSS group and that of all other subgroups ( P <0.012), the PI of the DDD group and that of DSPL ( P <0.001), and the STA of the LDH/DSPL groups and that of the LSS/DDD group ( P <0.005). Conclusions: We found all the constant anatomic parameters to be specific for distinct types of degeneration, suggesting pelvis shape is a predisposing factor for their development. Level of Evidence: Level III.